Climate Governance and Offshore Wind Energy in Brazil: Advances, Challenges and Future Perspectives - Melo, Rodrigo H. R. Quevedo; Melo, Ricardo H. R. Quevedo; Melo, Evanisa Fatima R. Q. (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – To analyze the development of offshore wind energy in Brazil, highlighting regulatory and institutional challenges, as well as opportunities for environmental governance in the context of global climate change. Methodology – A systematic and bibliometric literature review was conducted using ProKnow-C and Methodi Ordinati methods, applied to Scopus and Web of Science databases to identify the most relevant studies on offshore wind energy in Brazil. Originality/Relevance – This study addresses a gap in the integration between public policy, regulatory aspects, and renewable energy implementation in Brazil’s coastal areas, reinforcing the need for a multiscalar climate governance approach. Results – The findings indicate Brazil’s high technical potential for offshore wind energy and identify the lack of specific regulation, external technology dependence, and interinstitutional planning deficiencies as key barriers. Theoretical/Methodological Contributions – The use of ProKnow-C and Methodi Ordinati offers a robust foundation for mapping scientific production and for structuring critical insights to inform public policy. Social and Environmental Contributions – This research supports a fair and clean energy transition in Brazil, providing key inputs for political and strategic decisions aimed at mitigating the impacts of climate change.